HUBUNGAN ANTARA RASA PERCAYA DIRI DENGAN HASIL BELAJAR PADA MATA PELAJARAN EKONOMI SISWA KELAS XI SEKOLAH MENENGAH ATAS KARYASEKADAUTAHUN PELAJARAN 2014/2015 - Dessy Triana Relita; Fransiska Regina (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2015)
The aim in this study was to determine the relationship between confidence with result learned in economy lesson class XI Sekadau High School in 2014/2015. The method used in quantitative method with a form of research sorrelation studies. Based on the average yield of confidence obtained for 79.05 of result it can be concluded that the selpconvidence of student quite well. While the results of the testresult student learning acquired at 87,54 so it can be conclude that the class XI were used sample had learning outcomes as very good. nResult obtained correlation coefficient the value of, 0,568 (the category is strong enough so that coefficient of determination amaunts to 32,26%. Meanwhile, the hypothesis is tested by testing t-test, with a gain of 5.47 t_test result, t_table 2.000, n 65 so dk 63, a (level of significance) 5 based on the t_test, the congclutions obtained is accepting Ha because t count ttable (5,47 2000). That is a significant relationship between confidenct with student night outcomes